Influence of thermal shock on the performance of B-staged epoxy bond coat for orthotropic steel bridge pavements. (2nd August 2021) - Xie, Hongfeng; Zhao, Ruikang; Wang, Rui; Xi, Zhonghua; Yuan, Zuanru; Zhang, Junsheng; Wang, Qingjun
Highlights: Thermal shock significantly increases the pull-off strength of the touch-dry BEBC. The hydrophilic touch-dry BEBC becomes hydrophobic after the thermal shock. Thermal shock greatly increases the Tg of the touch-dry BEBC. The touch-dry BEBC's tensile strength increases by about 300% after the thermal shock. Thermal shock temperature has a limited effect on the mechanical properties of BEBCs. Abstract: B-staged epoxy bond coat (BEBC) has been widely applied as a waterproof adhesive layer in the pavements of orthotropic steel bridges. During its application, the uncured BEBC layer was first paved on the surface of the steel deck or the bituminous surfacing and hot bituminous mixture would be constructed until the BEBC layer became touch-dry. In this paper, the impacts of thermal shock on the degree of cure (DOC), pull-off strength, hydrophilicity, glass transition temperature (Tg ), damping performance, thermal stability and mechanical behaviors of the touch-dry BEBC were investigated. Thermal shock greatly increased the DOC of the touch-dry BEBC and the touch-dry BEBC turned to be nearly fully cured after the thermal shock at a higher temperature. The pull-off strength of the touch-dry BEBC was remarkably improved by the thermal shock. After the thermal shock at 160 °C, the pull-off strengths at room temperature and at 60 °C of the touch-dry BEBC were increased by 584% and 914%, respectively. After the thermal shock, the contact angle of the touch-dry BEBC was greatly increased and the hydrophilicity of the touch-dry BEBC was converted to hydrophobicity. Thermal shock significantly increased the Tg of the touch-dry BEBC. Furthermore, the Tg of thermally shocked BEBCs slightly increased in the temperature. Thermal shock improved the damping performance of the fully cured BEBC. The tensile strength and toughness of the touch-dry BEBC were greatly improved by the thermal shock. However, thermal shock lowered the elongation at break of touch-dry BEBC. In the case of thermally shocked BEBCs, the temperature had a limited effect on the tensile strength, while the elongation at break increased in the temperature. The fracture energy first decreased in the temperature and increased after 150 °C. Maximum fracture energy appeared at 160 °C. After the thermal shock, the tensile strength of the touch-dry BEBC was increased by as much as 3-fold. The fracture energy of the BEBC thermally shocked at 160 °C was 182% greater than that of the touch-dry BEBC.